The ambivalent ally - Menon, A (1993)
My research examines the degree to which France was able to define an autonomous policy towards Nato in the period 1981-1992. In so doing, it addresses three central questions. What was the nature of French Alliance policy? To what extent did it prove capable of achieving the goals set for it by French policy makers? What constraints, if any, acted upon Alliance policy? My research, therefore, is intended to not only provide a detailed account of French Alliance policies, but also to offer a critical assessment of those policies, and explanation as to why they took the form they did. The thesis argues that French Alliance policy under Mitterrand displayed a marked continuity with the policies of his predecessors. However, whilst de Gaulle in particular had managed to reap substantial benefits from a policy involving non-integration into Nato military commands, a policy of 'independence' proved increasingly inappropriate as a means of achieving the goals set by French officials. A rapidly shifting international situation, along with a deteriorating domestic economic capacity to maintain an autonomous defence posture, rendered the traditional options of French Alliance policy increasingly dysfunctional. Based on this, the thesis goes on to illustrate the fact that the failure of policy to adapt to profoundly altered circumstances can be attributed to factors within France. Both the prevalent belief system in France - the so-called consensus on defence and foreign policy - and the nature of the policy-making process acted in such a way as to restrict the possibility of policy adaptation. Based on these findings, the thesis concludes by making some observations as to the limitations of many of the theories which deal with foreign policy.